2007
DOI: 10.1111/j.1574-6976.2007.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-acetic acid in microbial and microorganism-plant signaling

Abstract: Diverse bacterial species possess the ability to produce the auxin phytohormone indole-3-acetic acid (IAA). Different biosynthesis pathways have been identified and redundancy for IAA biosynthesis is widespread among plant-associated bacteria. Interactions between IAA-producing bacteria and plants lead to diverse outcomes on the plant side, varying from pathogenesis to phyto-stimulation. Reviewing the role of bacterial IAA in different microorganism-plant interactions highlights the fact that bacteria use this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
1,089
0
75

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,576 publications
(1,196 citation statements)
references
References 214 publications
(312 reference statements)
32
1,089
0
75
Order By: Relevance
“…A biossíntese de auxinas por bactérias acontece por diferentes rotas metabólicas (Spaepen et al, 2007), sendo o triptofano o principal precursor para a síntese de AIA -fato que explica os mais altos valores de indol detectados nos meios de cultivo que tiveram acréscimo de triptofano em relação aos que não o continham (Quadro 2). A biossíntese de fito-hormônios parece ser uma habilidade comum às bactérias diazotróficas, tem sido relatada em estirpes pertencentes aos gêneros Azotobacter (Martínez-Toledo et al, 1988), Rhizobium (Badenoch-Jones et al, 1982), Azospirillum (Martínez-Morales et al, 2003), Gluconacetobacter e Herbaspirillum (Bastián et al, 1998).…”
Section: Discussionunclassified
“…A biossíntese de auxinas por bactérias acontece por diferentes rotas metabólicas (Spaepen et al, 2007), sendo o triptofano o principal precursor para a síntese de AIA -fato que explica os mais altos valores de indol detectados nos meios de cultivo que tiveram acréscimo de triptofano em relação aos que não o continham (Quadro 2). A biossíntese de fito-hormônios parece ser uma habilidade comum às bactérias diazotróficas, tem sido relatada em estirpes pertencentes aos gêneros Azotobacter (Martínez-Toledo et al, 1988), Rhizobium (Badenoch-Jones et al, 1982), Azospirillum (Martínez-Morales et al, 2003), Gluconacetobacter e Herbaspirillum (Bastián et al, 1998).…”
Section: Discussionunclassified
“…The production of phytohormones is now well-documented by the free living and pathogenic bacterial species. Recently, it has also been suggested that IAA could also be a native signalling molecule in bacteria (Spaepen et al, 2007). The fact that several bacteria can catabolize IAA and use it as a sole source of carbon, nitrogen and energy (Leveau and Lindow, 2005), more information is needed about its possible role as signalling agent in bacteria.…”
Section: Occurrence Of Phytohormones In Bacteria and Fungimentioning
confidence: 99%
“…IAN can be hydrolyzed by nitrilase activity into auxins phenyl acetic acid and IAA. The hydrolysis of IAN into IAA by nitrilase activity is an extremely well characterized reaction in plants and bacteria (Bartel, 1997;Spaepen et al 2007). However, the IAN pathway is one of the several that have been identified for IAA biosynthesis (Chung and Tzeng, 2004).…”
Section: Nitrile Degrading Enzymes and Their Role In Plant Metabolismmentioning
confidence: 99%